Deciphering the Role of Expectations in the Process of Inflation Formation in the USA - Utku Altunöz (SAGE Open)
This study aims to decipher the pivotal role of expectations in the complex process of inflation formation within the United States. Considering recent economic developments, particularly the resurgence of inflation, understanding the dynamics of inflationary expectations becomes paramount. Through empirical analysis and a comprehensive review of relevant literature, this research investigates the intricate relationship between inflation and survey-based inflation expectations. It also explores whether recent economic dynamics have brought about any noteworthy changes in this relationship. The findings shed light on the significant impact of inflation expectations on inflationary outcomes, emphasizing the need for effective policy measures to manage and stabilize these expectations for maintaining price stability in the U.S. economy. This study contributes to the existing body of knowledge by providing valuable insights into the role of expectations in the inflation process and its implications for policymakers and economists alike. JEL Classification: E31, C32, C36.